Managing N Inputs and the Effect on N Losses Following Excretion in Open-Dirt Feedlots in Nebraska - Galen E. Erickson; Terry J. Klopfenstein (The Scientific World Journal)
Nutrition will play an important role in meeting the environmental challenges of beef cattle feedlots. Nutritionists are continually refining protein requirements, and have recently adopted a new metabolizable protein (MP) system to more efficiently use nitrogen (N) and allow more accurate diet formulation. Protein requirements vary by animal age and weight during the finishing period. Our hypothesis was that formulating diets with the MP system would decrease N inputs and lead to decreased excretion and losses. Comparing industry average diets (13.5% crude protein) to phase-fed diets formulated to not exceed MP requirements decreased N inputs by 10 to 20% for calves and yearlings without affecting average daily gain. Decreasing inputs led to a concomitant decrease in N excretion (12 to 21%) and losses (15 to 33%) in open-dirt feedlot pens. N losses are variable with time of year, with averages of 60 to 70% of excreted N lost during the summer months and 40% lost during the November to May feeding periods. Protein requirements are being refined continually as more research data are collected. However, formulation to meet protein requirements, but not exceed them, is an important nutritional management option for feedlots to become sustainable.